Surgically treated congenital cleft palate in a 4-month-old kitten: medium-term clinical and CT assessment. Issue 1 (March 2022) - Garnier, Paul; Viateau, Véronique; Manassero, Mathieu; Maurice, Emeline
Case summary: A 4-month-old female domestic shorthair kitten was presented for a congenital cleft palate causing nasal discharge and sneezing episodes. CT revealed a palatal bone defect involving 20% of the palatal area. Surgical correction of both the hard and soft palate defects was performed using the overlapping and medially positioned flap techniques, respectively. Complete healing of the wound and full resolution of the clinical signs occurred within a 1-month period. At 2 months postoperatively, two punctiform oronasal fistulae were observed rostrally without associated clinical signs. Control CT, performed 6 months postoperatively, revealed a 50% enlargement of the palatal bone defect. At 12 months postoperatively, the cat was still in good general condition without any clinical signs. Relevance and novel information: To the best of our knowledge, this is the first report to describe the treatment of a congenital cleft palate in a kitten using the overlapping flap technique with a successful medium-term clinical outcome, despite the formation of two oronasal fistulae. This suggests that, as in dogs, full restoration of oronasal compartmentation is not mandatory to achieve functional outcome. The increase of the palatal bone defect over time may play a role in late oronasal fistulae formation and should be considered for surgical planning.